2002
DOI: 10.1253/circj.66.80
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical Changes in High-Energy Phosphates During the Cardiac Cycle by Pacing-Gated 31P Nuclear Magnetic Resonance

Abstract: number of studies of myocardial energy metabolism using 31 P nuclear magnetic resonance (NMR) have been done on in vitro 1-4 and in vivo [5][6][7] hearts. Cyclical changes in the concentration of adenosine triphosphate (ATP), phosphocreatine (PCr), and inorganic phosphate (Pi) during the cardiac cycle have also been studied using the subject's blood pressure or electrocardiogram (ECG)-gated 31 P NMR techniques. Several studies have demonstrated that cyclical changes in ATP, PCr, and Pi arise in vitro [8][9][10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The predictions from the mathematical modeling of feedback mechanisms of regulation of mitochondrial respiration in cardiac cells are consistent with the results of in vivo studies of isolated and perfused rat’s heart by using the pacing-gated 31 PRMS [164,165]. These studies, not very often discussed, showed that under conditions of metabolic homeostasis [meaning constant average values of high energy phosphate metabolites (Figure 6A)] cardiac contraction cycles are associated with small-scale oscillations in ATP, PCr and Pi concentrations, depending on heart workload and the intrinsic kinetic properties of myosin (Figure 6B).…”
Section: Four General Characteristics Of Cardiac Energy Metabolism Tosupporting
confidence: 72%
See 1 more Smart Citation
“…The predictions from the mathematical modeling of feedback mechanisms of regulation of mitochondrial respiration in cardiac cells are consistent with the results of in vivo studies of isolated and perfused rat’s heart by using the pacing-gated 31 PRMS [164,165]. These studies, not very often discussed, showed that under conditions of metabolic homeostasis [meaning constant average values of high energy phosphate metabolites (Figure 6A)] cardiac contraction cycles are associated with small-scale oscillations in ATP, PCr and Pi concentrations, depending on heart workload and the intrinsic kinetic properties of myosin (Figure 6B).…”
Section: Four General Characteristics Of Cardiac Energy Metabolism Tosupporting
confidence: 72%
“…(B) shows oscillations of relative PCr content during cardiac cycle in perfused rat’s heart under conditions of metabolic stability. The curve marked by empty circles (○) is refitted using experimental data received by Honda et al ., 2002 in gate-pacing in [165] (with permission), only the mean values of metabolites are shown. (C) The origin of the problem of the compartmentalization of adenine nucleotides and metabolic energy sensing in cardiac cells.…”
Section: Figurementioning
confidence: 99%
“…Reaction velocities of myocardial ATP hydrolysis are not constant over the cardiac cycle, as suggested by older calorimetric studies indicating that about 75% of ATP consumption occurs during the systolic heart phase (11,12). Small changes in myocardial HEPs have been reported during the cardiac cycle in some perfused rat heart studies (13)(14)(15)(16)(17) and in one in vivo rat study (18), but the latter, to our knowledge, has not been reproduced (19). Cyclic changes in HEPs have not been observed in large animals or humans in vivo (20)(21)(22).…”
Section: Introductionmentioning
confidence: 80%
“…There has been much discussion about whether there are variations in HEPs during the cardiac cycle and, if so, whether they can be measured. Contradictory results have been published and hitherto no clear answer has arisen (13)(14)(15)(16)(17)(18)(19). The main focus of the current work was to investigate the flexibility of the CK reaction and the in vivo magnitude and accessibility of potential variations in HEPs and CK flux to detection by 31 P MRS methods.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations of PCr and Cr were in the order of 8–15% during the different phases of the cardiac cycle (Honda et al . ). Inorganic phosphate, Pi, is not consumed by the myofibrillar MMCK reaction and therefore diffuses freely and enters mitochondrial matrix via its carrier (PiC).…”
Section: Feedback Signalling Via Near‐equilibrium Enzymatic Phosphorymentioning
confidence: 97%